GROWTH, ANATOMY AND PHYSIOLOGY OF COFFEE PLANTS INTOXICATED BY THE HERBICIDE GLYPHOSATE - Castanheira, Dalyse Toledo; Alecrim, Ademilson de Oliveira; Voltolini, Giovani Belutti; Rezende, Tiago Teruel; Netto, Pedro Menicucci; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 2019)
Weed control is fundamental in coffee cultivation due to their high interference, competing with the crop for water, light and nutrients. Among the control methods used, chemical control is highlighted, due to its high efficiency and low cost. However, due to application failures, herbicide drift phytotoxicity is common. Aiming at the search for selective active ingredients in coffee, the objective of this study was to evaluate the selectivity of the active ingredient Glyphosate in young coffee plants. The experiment was carried out in a greenhouse with ‘Topázio MG1190’ coffee plants (Coffea arabica L.), cultivated in pots with an 11 L-substrate capacity. The statistical design was RBD, with four replications and four doses of the herbicide, making up 16 experimental plots. Each plot consisted of three plants. The treatments were: (i) 0%; (ii) 10%; (iii) 25% and (iv) 50% of the commercial dose of the herbicide Glyphosate. The evaluations were performed at 104 days after application of the treatments. Growth, morphological, physiological and anatomical characteristics were evaluated. The collected data were analyzed using the SISVAR software. The effect of glyphosate drift impairs plant growth. However, after 104 days of intoxication, there is no longer any effect on the physiology and leaf anatomy of coffee trees.